2014
DOI: 10.4149/neo_2014_085
|View full text |Cite
|
Sign up to set email alerts
|

Realgar (As4S4) nanoparticles and arsenic trioxide (As2O3) induced autophagy and apoptosis in human melanoma cells in vitro

Abstract: The aim of the present study was to compare the effect of realgar nanoparticles and arsenic trioxide (ATO) on viability, DNA damage, proliferation, autophagy and apoptosis in the human melanoma cell lines BOWES and A375. The application of various flow cytometric methods for measurements cell viability, DNA cell cycle, mitochondrial potential, lysosomal activity, and intracellular content of glutathione was used. In addition, quantitative PCR, western blotting and multiplex bead array analyses were applied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…42 Realgar NPs induced autophagy at lower dosage and apoptosis at higher concentration in melanoma cell lines. 43 Consistent with these previous studies, the results revealed that the ratio of LC3-II/LC3-I was significantly increased, whereas the expression of p62 was decreased in K562 cells after realgar NP treatment. PI3K/Akt/mTOR is a key signaling pathway in regulating homeostasis of mammalian cells.…”
supporting
confidence: 81%
“…42 Realgar NPs induced autophagy at lower dosage and apoptosis at higher concentration in melanoma cell lines. 43 Consistent with these previous studies, the results revealed that the ratio of LC3-II/LC3-I was significantly increased, whereas the expression of p62 was decreased in K562 cells after realgar NP treatment. PI3K/Akt/mTOR is a key signaling pathway in regulating homeostasis of mammalian cells.…”
supporting
confidence: 81%
“…26 Recently, the molecular mechanisms of realgar nanoparticlemediated melanoma cell killing were described, including autophagy and apoptosis, induction, as well as modulation of NF-kB, Akt, and MAP kinase signaling pathways. 27 In our other work, we also found that RQDs are effective in induction of apoptosis protein Bax and suppression of antiapoptotic protein Bcl-2 in HepG2 cells.…”
Section: Discussionmentioning
confidence: 81%
“…It contains Realgar (α-As4S4, an arsenic sulfide mineral), Bos taurus domestius Gmelin (dried bovine gallstones), Borneol (a terpene) and cinobufagin venom toad organic material (from toad gland extract). Notably, Realgar and Borneol have been reported to have anti-cancer activity in various cancer cell lines (13,14). Additionally, Borneol acts as a drug absorber (15), and Bos taurus domesticus Gmelin has been used to remove toxins from the body (see ).…”
Section: Resultsmentioning
confidence: 99%